2014
DOI: 10.1152/jn.00212.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal striatum metabotropic glutamate receptor 8 affects nocifensive responses and rostral ventromedial medulla cell activity in neuropathic pain conditions

Abstract: In SNI rats, which showed a reduction of the mechanical withdrawal threshold, intra-DS microinjection of (S)-3,4-DCPG inhibited the ongoing and tail flick-evoked activity of the ON cells while increasing the activity of the OFF cells. AZ12216052, a selective mGluR 8 positive allosteric modulator (PAM), behaved like (S)-3,4-DCPG in increasing tail flick latency and OFF cell activity and decreasing ON cell activity in SNI rats only but was less potent. VU0155041, a selective mGluR 4 PAM, was ineffective in chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…Two types of neurons in the RVM, the so-called ON and OFF cells, are involved in the modulation of nociception at the spinal level (Fields et al 1991(Fields et al , 1995. In various pain models, including diabetes, chronic constriction injury, spared nerve injury, formalin, and carrageenan pain models, the spontaneous activity of pain facilitatory ON cells in the RVM is increased, whereas the spontaneous activity of the pain inhibitory OFF cells is decreased (de Novellis et al 2005;Palazzo et al 2011aPalazzo et al ,b, 2012Silva et al 2013;Rossi et al 2014;Marabese et al 2018). The decrease in the spontaneous activity of OFF cells indicates that the tonic pain inhibition exerted by RVM neurons is lost under the pain state.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of neurons in the RVM, the so-called ON and OFF cells, are involved in the modulation of nociception at the spinal level (Fields et al 1991(Fields et al , 1995. In various pain models, including diabetes, chronic constriction injury, spared nerve injury, formalin, and carrageenan pain models, the spontaneous activity of pain facilitatory ON cells in the RVM is increased, whereas the spontaneous activity of the pain inhibitory OFF cells is decreased (de Novellis et al 2005;Palazzo et al 2011aPalazzo et al ,b, 2012Silva et al 2013;Rossi et al 2014;Marabese et al 2018). The decrease in the spontaneous activity of OFF cells indicates that the tonic pain inhibition exerted by RVM neurons is lost under the pain state.…”
Section: Discussionmentioning
confidence: 99%
“…Local injections of VU015504 into the dorsal striatum in sham and neuropathic rats failed to change the tail flick latency or activity of the ON and OFF cells of the rostral ventromedial medulla (RVM) (Rossi et al . ). ON cells are excited by nociceptive stimuli and inhibited by centrally acting analgesics, whereas OFF cells are inhibited by noxious stimuli and activated by analgesics.…”
Section: Group III Mglurs and Painmentioning
confidence: 97%
“…; Rossi et al . ). These observations raise the distinct possibility that a NK1R and ERK1/2 phosphorylation‐dependent mechanism modulate the RVM pain facilitatory pathway.…”
Section: Discussionmentioning
confidence: 97%
“…In the mouse brain, axons from the striatum directly project to the RVM (Wall et al 2013). In addition, studies utilizing models of neuropathic pain have shown that striatal neurons directly modulate activity of RVM neurons involved in descending pain modulation (Barcel o et al 2010;Rossi et al 2013). These observations raise the distinct possibility that a NK1R and ERK1/2 phosphorylation-dependent mechanism modulate the RVM pain facilitatory pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation